Analyzing risky behaviors among different minority and majority race in teenagers in the USA using latent classes - Aslam, Zeeshan; Asim, Muhammad; Javaid, Iqra; Rasheed, Faisal; Akhter, Muhammad Naveed (Frontiers in Behavioral Neuroscience, 2023)
Objective: This study is to ascertain any inconsistencies in the trend of co-occurrence by sex of teenage health risk behaviour patterns such as smoking, behaviours contributing to deliberate and unintentional injuries, risky sexual behaviour, and sedentary lifestyle. Methods: The study purpose was accomplished using Youth Risk Behavior Surveillance System (YRBSS) 2013 data. A Latent Class Analysis (LCA) was conducted for the entire sample of teenagers as well as separately for each sex. Results: Over half of teenagers in this subset admitted to smoking marijuana, and there was a significant probability of current cigarette usage. In this subset, more than half participated in hazardous sexual behaviours, such as not wearing a condom during their most recent encounter. Based on their involvement in dangerous conduct, boys were divided into three different categories, while girls were divided between four different subsets. Conclusion: Regardless of gender, various risk behaviours among teenagers are connected. However, gender variations in the higher risk of particular trends, such as mood disorders and depression amongst girls, underline the significance of creating treatments that take into account adolescent demographics.